Synchronous reconstruction of bilateral osteoradionecrosis of the mandible using a single fibular osteocutaneous flap in patients with nasopharyngeal carcinoma - Fan, Song; Wang, You-Yuan; Lin, Zhao-Yu; Zhang, Da-Ming; Yu, Xin; Chen, Wei-Xiong; Zhong, Jiang-Long; Li, Qun-Xing; Feng, Yu-Huan; Chen, Wei-Liang; Pan, Chao-Bin; Dias-Ribeiro, Eduardo [UNESP]; et al. (Wiley-Blackwell, 2015)
The reconstruction of bilateral osteoradionecrosis (ORN) of mandibular defects using a single free bone flap is rarely performed because extensively radiated neck tissue with severe fibrosis is usually unsuitable for vascularized reconstruction. Thirty-one patients with nasopharyngeal carcinoma (NPC) underwent bilateral reconstruction of advanced ORN in the mandible using a single fibular osteocutaneous flap. Clinical factors associated with the operation were assessed, including classification of mandible defects, types of recipient vessels, perioperative complications, and postoperative outcomes. All of the fibular osteocutaneous flaps survived completely, with the exception of 1 inner skin paddle that presented partial necrosis in a reconstruction of through-and-through defects. All patients experienced an improvement in cosmetic results 6 months after the reconstruction, whereas 23 patients experienced improved mouth opening compared to the preoperative condition. Advanced bilateral ORN in patients with NPC could be synchronously reconstructed with a single fibular osteocutaneous flap. © 2015 Wiley Periodicals, Inc. Head Neck, 2015.
Keywords: Bilateral osteoradionecrosis; Fibular osteocutaneous flap; Mandible; Nasopharyngeal carcinoma; Synchronous reconstruction